Novel swellable polymer of orchidaceae family for gastroretentive drug delivery of famotidine - Razavi M; Nyamathulla S; Karimian H; Noordin MI (Dove Medical Press, 2014)
Mahboubeh Razavi,1 Shaik Nyamathulla,1,2 Hamed Karimian,1 Mohamed Ibrahim Noordin1,2 1Department of Pharmacy, Faculty of Medicine, 2Center for Natural Products and Drug Discovery, Department of Chemistry, Faculty of Science, University of Malaya, Kuala Lumpur, Malaysia Abstract: This study aimed to develop hydrophilic, gastroretentive matrix tablets of famotidine with good floating and swelling properties. A novel gastroretentive drug delivery formulation was designed using salep, also known as salepi, a flour obtained from grinding dried palmate tubers of Orchis morio var mascula (Orchidaceae family). The main polysaccharide content of salep is glucomannan, highly soluble in cold and hot water, which forms a viscous solution. Salep was characterized for physicochemical properties, thermal stability, chemical interaction, and surface morphology using X-ray diffraction analysis, differential scanning calorimetry, Fourier transform infrared spectroscopy, and scanning electron microscopy. Ten different formulations (S1–S10) were prepared using famotidine to salep ratios from 1:0.5 to 1:5. Results demonstrated that all formulations were able to sustain the drug release for more than 24 hours. The S5 formulation, with a famotidine to salep ratio of 1:2.5, had the shortest floating lag time of 35 seconds and 100% drug release within 24 hours. The dissolution data were fitted into popular mathematical models to assess the mechanism of drug release. S5 showed Zero order release (R=0.9746) with Higuchi diffusion (R=0.9428). We conclude that salep, a novel polymer, can be used in controlled release formulations to sustain release for 24 hours, due to inherent swelling and gelling properties. Keywords: famotidine, floating matrix tablets, gastroretentive drug delivery, orchis, salep